2022
DOI: 10.2147/dmso.s350579
|View full text |Cite
|
Sign up to set email alerts
|

The Perirenal Fat Thickness Was Associated with Nonalcoholic Fatty Liver Disease in Patients with Type 2 Diabetes Mellitus

Abstract: Purpose Obesity is an important risk factor for nonalcoholic fatty liver disease (NAFLD). Perirenal fat and paranephric fat were seldom studied in NAFLD. We aimed to explore the relationship between perirenal fat thickness (PrFT) and paranephric fat thickness (PnFT) and NAFLD in patients with type 2 diabetes mellitus (T2DM). Patients and Methods A total of 493 diabetic patients including 231 NAFLD patients were enrolled in our study from September 2019 to December 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Insulin sensitivity and glucose tolerance were observed to improve in animal trials when SAT was transplanted into the visceral cavity [37]. VAT produces pro-inflammatory cytokines, recruiting more pro-inflammatory macrophages and secreting more vasoconstrictive mediators than SAT [4,38,39]. Studies have shown that in people with the same BMI, the risk of CVD increases with the accumulation of visceral fat [40].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity and glucose tolerance were observed to improve in animal trials when SAT was transplanted into the visceral cavity [37]. VAT produces pro-inflammatory cytokines, recruiting more pro-inflammatory macrophages and secreting more vasoconstrictive mediators than SAT [4,38,39]. Studies have shown that in people with the same BMI, the risk of CVD increases with the accumulation of visceral fat [40].…”
Section: Discussionmentioning
confidence: 99%